Analisis Perilaku Wajib Pajak Terhadap Niat Menggunakan E-Filling dan Kepatuhan Wajib Pajak (Studi Pada Wajib Pajak Dengan Profesi Sebagai Dosen) - Muhammad Abadan Syakura (Faculty of Economics and Business Mulawarman University, 2017)
To improve taxpayer compliance, the government has improved the tax administration system in order to facilitate taxpayers such as by developing IT-based tax administration system such as e-filing for SPT PPh and e-invoice for VAT. However, it still can not improve taxpayer compliance. This study aims to determine what affects the compliance behavior of the taxpayers (especially those who work as teachers) with mediated by the intention of using e-filling. Based on the phenomenon of taxpayer noncompliance and inconsistent results of the above research, this research tries to empirically test the tax compliance model using variables of tax administration complexity, tax knowledge, and satisfaction by focusing on taxpayer compliance of individual lecturer profession in Samarinda City. Taxpayer compliance is reflected in the behavior of taxpayers / individuals in fulfilling their tax obligations. This study uses the theory of planned behavior to observe what factors affect the behavior of taxpayers who prioritize the benefits of tax paid. This study obtains empirical evidence that tax knowledge and satisfaction affect the intention of using e-filling and taxpayer compliance. While the complexity of taxation does not affect the intention of using e-filling. In addition, the intention of using e-filling proven to mediate the knowledge and taxpayer's satisfaction in influencing taxpayer compliance. The results of this study can be used by tax authorities to be able to improve the performance and services provided to taxpayers in order to improve voluntary compliance.Keywords: E-filling, Voluntary Compliance, Theory of Planned Behavior, Deterrence Theory